The Effectiveness of Using Instagram Social Media to Improve Vocabulary Mastery of Eleventh-Grade Students at SMA Negeri 4 Purworejo in the Academic Year of 2025/2026 - Mu’aafi, Dhiya’ulhaq Yaskur; Sudar, Sudar; Johan, Andrian Nuriza (Dinasti Research, 2026)
The Effectiveness of Using Instagram Social Media to Improve Vocabulary Mastery of Eleventh Grade Students at SMA Negeri 4 Purworejo in The Academic Year of 2025/2026. This study aims to examine the effectiveness of using Instagram as a learning medium to improve vocabulary mastery among eleventh-grade students at SMA Negeri 4 Purworejo. The research employed a quantitative approach with a one-group pre-test and post-test design. The sample consisted of 30 eleventh-grade students selected from the population. Data were collected using a multiple-choice vocabulary test consisting of 30 items, administered before and after the treatment. The treatment involved vocabulary instruction using Instagram features such as posts, captions, and visual content. The collected data were analyzed using descriptive statistics and paired sample t-test. The results showed that the mean score of students increased from 60.33 in the pre-test to 78.67 in the post-test. The paired sample t-test result indicated a significance value of 0.000, which is lower than 0.05, meaning that there is a significant difference between students’ vocabulary mastery before and after using Instagram. Therefore, it can be concluded that the use of Instagram social media is effective in improving vocabulary mastery of eleventh-grade students at SMA Negeri 4 Purworejo